Missing documentation in breast cancer survivors: genitourinary syndrome of menopause. Issue 12 (December 2017) - Cook, Elise D.; Iglehart, Elena I.; Baum, George; Schover, Leslie L.; Newman, Lonzetta L.
Abstract: Objective: Breast cancer survivors often take hormonal treatments to prevent the recurrence of breast cancer, particularly aromatase inhibitors that can worsen the symptoms of genitourinary syndrome of menopause (GSM) such as dyspareunia, dysuria, and urinary incontinence, all of which may adversely affect survivors' quality of life. Few breast cancer survivors experiencing GSM receive adequate assessment or treatment. Methods: In this descriptive study, we reviewed medical records for documented GSM and any treatments administered or referrals for treatment in 800 female patients who visited the Breast Cancer Survivorship Clinic at a comprehensive cancer center between July 1, 2010 and June 30, 2011, either at least 5 years after completion of treatment for invasive breast cancer or at least 6 months after completion of treatment for ductal carcinoma in situ. Results: Of the 279 patients with documented symptoms of vaginal atrophy, only 111 (39.8%) had documentation of having received any form of treatment or referral. Of the 71 patients with documented symptoms of urinary tract atrophy, only 33.8% had documentation of having received treatment or referral for treatment. Conclusion: Breast cancer survivors often experience GSM due to lack of estrogen. The worrisome lack of documentation of assessment or treatment for GSM in a large breast cancer survivorship practice reveals missed opportunities to improve quality of life. Dissemination of recent progress in the development of GSM assessment tools, patient handouts, and new treatments to providers who care for breast cancer survivors is needed to improve this process.